Sediment examination of urine without physical-chemical alterations - Diego Z. Nascimento; Mayara D. Pickler; Gabriela M. Marques; Fabiana S. Trevisol; Ana Luisa O. Martins (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Introduction: It is from the urine sediment examination that many conclusions are drawn by the professional responsible for diagnosis. Because that is a test frequently run in laboratories, it is desirable to reduce costs and time to exam sediment in urine samples considered normal. Objectives: To evaluate the importance of sediment microscopy in urine without physical and chemical alterations. Material and method: This is an epidemiological study of a cross-sectional design developed at a college laboratory based on reports of urine tests performed from January to July, 2017. For comparison between means, Student's t-test, Pearson's chi-square test and Spearman's correlation were done. The level of significance was 5%. Results: We analyzed 7,734 urine reports, with 2,530 (32.7%) results without physical-chemical changes. Patients had a mean age of 39 (± 23) years, most of them were males (61.7%). Regarding leukocyte quantification, 2.3% of the patients had a number higher than the reference values, and in relation to red blood cells, 1.7% of the patients exceeded these values. It was observed that the amount of leukocytes found in the urine specimens without physical-chemical alterations (p < 0.007) was reduced by 0.4 with each year of age. Conclusion: From the data of the present study, one can conclude that the majority of patients without physical-chemical changes do not have any changes of clinical relevance in sediment analysis.